Nutritional status among children and adolescents aged 6–18 years of Kolam tribe of Andhra Pradesh, India - Bharthi, K.; Ghritlahre, Manisha; Das, Subal; Bose, Kaushik (Anthropological Review, 2017)
Malnutrition has become one of the serious problems among children and adolescents internationally, especially in developing countries. India, a developing country covers 40% of undernourished children of the world. In India, tribal population is among the most deprived and undernourished people. The present study shows the prevalence of undernutrition among Kolam tribal children and adolescents by comparing different Body Mass Index (BMI) cut off points. Age and sex specific nutritional status of studied population shows 15.01% boys and 18.35% girls are in Chronic Energy Deficiency (CED) III category, 16.22% boys and 19.32% girls are in CEDII, 31.71% boys and 2.72% girls are in CEDI only 0.96% boys and 1.69% girls are in overweight category respectively. Undernutrition is not limited to young children, even adults are also severely underweight in developing countries. Health and nutrition of today’s adolescent girls may have great impact on the quality of next generation. Proper nutritional programs and health policies are needed to be implemented among tribals to solve the problem of undernutrition and similar studies should be planned in other underprivileged sections worldwide.